Research on Bogie Frame Lateral Instability of High-Speed Railway Vehicle - Chen Wang; Shihui Luo; Ziqiang Xu; Chang Gao; Weihua Ma (Shock and Vibration)
In order to find out the reason for the bogie frame instability alarm in the high-speed railway vehicle, the influence of wheel tread profile of the unstable vehicle was investigated. By means of wheel-rail contact analysis and dynamics simulation, the effect of tread wear on the bogie frame lateral stability was studied. The result indicates that the concave wear of tread is gradually aggravated with the increase of operation mileage; meanwhile the wheel-rail equivalent conicity also increases. For the rail which has not been grinded for a long time, the wear of gauge corner and wide-worn zone is relatively severe; the matching equivalent conicity is 0.31-0.4 between the worn rail and the concave-worn-tread wheel set. The equivalent conicity between the grinded rail and the concave-worn tread is below 0.25; the equivalent conicities are always below 0.1 between the reprofiled wheel set and various rails. The result of the line test indicates that the lateral acceleration of bogie frame corresponding to the worn wheel-rail can reach 8.5m/s2, and the acceleration after the grinding is reduced below 4.5m/s2. By dynamics simulation, it turns out that the unreasonable wheel-rail matching relationship is the major cause of the bogie frame lateral alarm. With the tread-concave wear being aggravated, the equivalent conicity of wheel-rail matching constantly increases, which leads to the bogie frame lateral instability and then the frame instability alarm.